Climatology, bioclimatology and vegetation cover: tools to mitigate climate change in olive groves - Cano-Ortiz, Ana (2022)
This work establishes the relationship between bioclimatology and agronomy. Bioclimatic indices are obtained for several areas under olive cultivation and correlated with olive yields. Due to the effect of climate change on cultivation and the high economic losses it produces, we propose a sustainable development model for the territorial classification of crops based on bioclimatic knowledge. Bioclimatic diagrams are prepared to provide information on water stress in crops so that irrigation can be carried out at the most effective time, a measure that has been shown to lead to water and energy savings for growers. In addition to this development model, we propose the application of non-aggressive cultivation techniques such as the use of living plant cover to ensure the protection of the soil and avoid losses due to climate irregularities. Studies conducted up to the present on applied bioclimatology have yielded promising results in the fields of farming and forestry. The maps and bioclimatic indices of Professor Rivas-Martínez, Ic, Io and It/Itc, are essential for bioclimatic classification. The agricultural development model with a bioclimatic basis ensures economic savings for growers and minimizes the environmental impact of cultivation. In the case of olive cultivation we detected that in 2005 all the cultivated areas that were not in their thermoclimatic optimum were damaged by frost. The widespread cultivation of olive groves in the Mediterranean basin, and mainly in the south of Spain, is reason enough to establish a relationship between its production and its bioclimatic environment. The ombroclimatic study in certain localities under olive cultivation shows that areas with Io <2.5 are unproductive (Jodar, Tabernas), and that their low Io value needs to be supplemented with irrigation water. This means extracting water from aquifers for agricultural use, when the current climate irregularities do not allow the excessive use of subsoil water. For the time being the only way of mitigating this situation is with sustainable development, which requires a bioclimatic understanding of the territory; and the use of appropriate cultivation techniques, including herbaceous plant covers. In this last case a knowledge of the plant associations in the phytosociological class Stellarietea mediae constitutes the basis for establishing either natural or sown vegetation cover.